2003
DOI: 10.2134/agronj2003.1432
|View full text |Cite
|
Sign up to set email alerts
|

The Model‐Document‐View Architecture and Its Application in Visual Rice Growth Model

Abstract: The object‐oriented paradigm (OOP) provides a methodology for resolving a crop simulation system into subsystems and processes so that a modeler can design objects to simulate their behaviors. Many objects are also devoted to producing object‐oriented user interfaces to simplify operation of the simulator. How to integrate these objects on a higher level and how to make models and user interfaces communicate efficiently are the issues addressed in the current research. The proposed model‐document‐view (MDV) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There have been many studies on the time-course patterns of stem number, LAI and dry matter accumulation in rice, along with their quantitative relationships to different cultivars and cultural conditions, driven by growth dynamics and determined by carbohydrate supply of the crop (Rezaul, 1998;Zhong et al, 1999). Several simulation models have been developed for predicting the eco-physiological processes of growth and yield formation in rice under different conditions (Bouman et al, 2001;Meng et al, 2003;Mi et al, 2003). Some investigators further suggested optimal values of key growth characters for the specifi c rice varieties and conditions by the method of simulation and optimization (Horie et al, 1992).…”
mentioning
confidence: 99%
“…There have been many studies on the time-course patterns of stem number, LAI and dry matter accumulation in rice, along with their quantitative relationships to different cultivars and cultural conditions, driven by growth dynamics and determined by carbohydrate supply of the crop (Rezaul, 1998;Zhong et al, 1999). Several simulation models have been developed for predicting the eco-physiological processes of growth and yield formation in rice under different conditions (Bouman et al, 2001;Meng et al, 2003;Mi et al, 2003). Some investigators further suggested optimal values of key growth characters for the specifi c rice varieties and conditions by the method of simulation and optimization (Horie et al, 1992).…”
mentioning
confidence: 99%
“…A proper software design, targeted at achieving an intrinsic reusability of software units, can lead to sharing knowledge in an immediately reusable form. Several studies have been recently published (Acock et al, 1999;Rossiter and Riha, 1999;Donatelli et al, 2003;Fila et al, 2003;Mi et al, 2003), mostly designing reusable dynamic link libraries within the COM (Component Object Model) technology of Windows (www.microsoft.com/com; verified 10 July 2006). Component-oriented programming, which combines object-oriented and modular features, is becoming the leading methodology in developing systems in a variety of domains, including agro-ecological modeling (Argent, 2004).…”
mentioning
confidence: 99%